Designing spirobifullerene core based three‐dimensional cross shape acceptor materials with promising photovoltaic properties for high‐efficiency organic solar cells. Issue 22 (13th July 2020) - Khan, Muhammad Usman; Mehboob, Muhammad Yasir; Hussain, Riaz; Afzal, Zainab; Khalid, Muhammad; Adnan, Muhammad
Abstract: The development of organic electron acceptor materials is one of the key factors for realizing high‐performance organic solar cells (OSCs). Nonfullerene electron acceptors, compared to traditional fullerene acceptor materials, have gained much impetus owing to their better optoelectronic tunabilities and lower cost, as well as higher stability. Therefore, 5 three‐dimensional (3D) cross‐shaped acceptor materials having a spirobifullerene core flanked with 2, 1, 3‐benzothiadiazole are designed from a recently synthesized highly efficient acceptor molecule SF(BR) 4 and are investigated in detail with regard to their use as acceptor molecules in OSCs. The density functional theory (DFT) and time‐dependent DFT (TDDFT) calculations have been performed for the estimation of frontier molecular orbital (FMO) analysis, density of states analysis, reorganization energies of electron and hole, dipole moment, open‐circuit voltage, photo‐physical characteristics, and transition density matrix analysis. In addition, the structure‐property relationship is studied, and the influence of end‐capped acceptor modifications on photovoltaic, photo‐physical, and electronic properties of newly selected molecules (H1‐H5 ) is calculated and compared with reference (R ) acceptor molecule SF(BR) 4 . The structural tailoring at terminals was found to effectively tune the FMO band gap, energy levels, absorption spectra, open‐circuit voltage, reorganization energy, and binding energy value in selected molecules H1 to H5 . The 3D cross‐shaped molecules H1 to H5 suppress the intermolecular aggregation in PTB7‐Th blend, which leads to high efficiency of acceptor material H1 to H5 in OSCs. Consequently, better optoelectronic properties are achieved from designed molecules H1 to H5 . It is proposed that the conceptualized molecules are superior than highly efficient spirobifullerene core‐based SF(BR) 4 acceptor molecules and, thus, are recommended to experiments for future developments of highly efficient solar cells. Abstract : Five 3D cross‐shaped acceptors materials (H1‐H5 ) have been designed for solar cell applications. The structure‐property relationship is studied, and the influence of end‐capped acceptor modifications on the photovoltaic, photo‐physical, and electronic properties of newly selected molecules (H1‐H5 ) is calculated and compared with SF(BR) 4 . All designed molecules exhibit better photovoltaic properties than recently synthesized SF(BR) 4 molecules.